Urban and Peri-Urban Agriculture Practices in Different Countries: A Systematic Literature Review - Pugazhendhi, Kaveya; Hameed, Aisha; Mansingh J, Paul (Journal of Agricultural Extension Management, 2023)
Urban and peri-urban agriculture (UPA) is the activities carried out on land and in other locations within the cities and their surroundings that produce food and other products through agricultural production and associated processes. A systematic literature review on the urban and peri-urban agriculture practices followed in different countries using the Preferred Reporting Items for Systematic Reviews and MetaAnalysis (PRISMA) method is presented in this paper. Using several search strings and advanced searches, 1014 articles were identified from the Scopus database. Later using inclusion, exclusion, and quality assessment criteria, 32 articles relevant to the subject were included in the study. This systematic review identified the UPA practices in nearly 20 countries like The Netherlands, Kenya, Italy, Nepal, India, Brazil, Ethiopia, Zimbabwe, Argentina, Nigeria, and a few more worldwide. The practices followed in the countries and the critical reasons behind the practices are analyzed in the study. However, in most peri-urban areas, agriculture is followed only for family consumption or for selling the produce in the local markets or communities. Vegetable gardening and mixed farming are the prevalent agricultural practices in urban and peri-urban areas. Co-operative model worker’s gardens and collective plots of the shared garden are practiced in France that encourage the united farm work of villagers. UPA is reported to reduce the food miles and supply chain thereby reducing the carbon footprint. Farms cultivating many short-duration crops in a single field for multiple seasons increase soil fertility. Farming kits like ‘Do-it-yourself’ horticultural kits in India and ‘Mushroom growing kits’ in Switzerland and other such government kits were used to promote UPA. A greater number of studies were found in the eastern countries when compared with other countries around the world. Further research is required to identify the practices followed in other countries